Pelikula a documentary on Philippine film - Concepcion, Rowena E.; Umali, Gina C.; Sotto, Agustin L. (Tuklas Sining, 1989)
Traces the history of moviemaking in the Philippines, featuring film clips from movies produced from the 1930's to the present, representing the major commercial genres- musical, melodrama, comedy and action movies- as well as the new cinema and the alternative films.